NOTES AND DOCUMENTS FOR THE HISTORY OF NATURAL SCIENCE IN MEXICO I LONG DASH THE STATUTES OF THE ORIGINAL SOCIEDAD MEXICANA DE HISTORIA NATURAL - BELTRAN, ENRIQUE (Universidad Nacional Autónoma de Mexico, CD MEXICO, DF, MEX, 1943)
Plagiorchis (Multiglandularis) muris (Tanabe, 1922) and Limatulum limatulum (Braun, 1900) are redescribed and 2 new Trematodes of the bats, Prosthodendrium emollidum and OCHOTERENATREMA labda, are described
REV SOC MEX HIST NAT
Keywords: NOTES, DOCUMENTS, HISTORY, NATURAL SCIENCE, MEXICO I[LONG DASH], STATUTES, ORIGINAL SOCIEDAD MEXICANA DE HISTORIA NATURAL; CIENCIAS DE LA VIDA